Periodontal Disease-Induced Atherosclerosis and Oxidative Stress - Tomoko Kurita-Ochiai; Ru Jia; Yu Cai; Yohei Yamaguchi; Masafumi Yamamoto (MDPI AG, 2015)
Periodontal disease is a highly prevalent disorder affecting up to 80% of the global population. Recent epidemiological studies have shown an association between periodontal disease and cardiovascular disease, as oxidative stress plays an important role in chronic inflammatory diseases such as periodontal disease and cardiovascular disease. In this review, we focus on the mechanisms by which periodontopathic bacteria cause chronic inflammation through the enhancement of oxidative stress and accelerate cardiovascular disease. Furthermore, we comment on the antioxidative activity of catechin in atherosclerosis accelerated by periodontitis.